Regulatory B cells prevent and reverse allergic airway inflammation via FoxP3-positive T regulatory cells in a murine model. - FALLON, PADRAIC; SAUNDERS, SEAN; AMU, SYLVIE; ATZBERGER, ANN (My University, 2010)
BACKGROUND: Parasitic helminth infections of humans have been shown to suppress the immune response to allergens. Experimentally, infection of mice with the helminth Schistosoma mansoni prevents allergic airway inflammation and anaphylaxis via IL-10 and B cells. OBJECTIVE: To identify and characterize the specific helminth-induced regulatory B-cell subpopulation and determine the mechanism by which these regulatory B cells suppress allergic airway inflammation. METHODS: IL-10-producing B cells from the spleens of helminth-infected mice were phenotyped, isolated, and transferred to ovalbumin-sensitized mice, and their ability to modulate allergic airway inflammation was analyzed. RESULTS: S mansoni infection induced IL-10-producing CD1d(high) regulatory B cells that could prevent ovalbumin-induced allergic airway inflammation following passive transfer to ovalbumin-sensitized recipients. The capacity of regulatory B cells to suppress allergic airway inflammation was dependent on the expression of CD1d, and they functioned via an IL-10-mediated mechanism. Regulatory B cells induced pulmonary infiltration of CD4(+)CD25(+) forkhead box protein 3(+) regulatory T cells, independent of TGF-beta, thereby suppressing allergic airway inflammation. Regulatory B cells that were generated ex vivo also suppressed the development of allergic airway inflammation. Furthermore, the transfer of regulatory B cells reversed established airway inflammation in ovalbumin-sensitized mice. CONCLUSION: We have generated in vivo and ex vivo a regulatory B cell that can prevent or reverse allergen-induced airway inflammation via regulatory T cells.
PUBLISHED
PMID: 20304473
Keywords: Immunology and Infection; regulatory T cells; Immunology, Inflammation & Infection